Three Sports Complexes in Krasnodar Krai - Churilov, Victor (project baikal, 2017)
This collection presents three sports venues recently designed by Victor Churilov’s bureau. Their architecture is functional, and their composition is very rational. The authors have created a row of landmark structures that harmonize with the landscape of Kuban.